Persistence of flubendiamide residues in the cabbage field soil under semi-arid region of Rajasthan - Hansa Kumari Jat; B.L. Jakhar; Arjun Lal Choudhary (Annals of Agricultural Research, 2022)
Flubendiamide be included in a novel class of insecticide, which used in control of lepidopteran pest complex of cabbage, such as cabbage white butterfly diamondback moth, cluster caterpillar et. A study was undertaken at Rajasthan Agricultural Research Institute, Durgapura, Jaipur during Rabi, 2020 to find outthe residue persistence of flubendiamide residues in the soil of cabbage field, when sprayed at its recommended dose (flubendiamide 18.24 g.a.i. ha-1) and double of the recommended dose (flubendiamide 36.48 g.a.i. ha-1). The samples were extracted with acetonitrile and cleaned up using a modified QuEChERS method and the residues were analyzed by HPLC. The residues level of flubendiamide in cabbage field soil collected at harvest time of cabbage crop were below the detectable level (BDL) at the recommended dose and double of the recommended dose, respectively.